The Impact of Market and Policy Instability on Price Transmission between Wheat and Flour in Ukraine - Brummer, Bernhard; von Cramon-Taubadel, Stephan; Zorya, Sergiy (2012)
Analysis of price transmission in transition countries is often complicated by unstable policy environments. We use a Markov-switching vector error-correction model (MSVECM) to model multiple regime shifts in the relationship between wheat and wheat flour prices in Ukraine from June 2000 to November 2004. Unlike common alternative error correction specifications, the MSVECM does not require an explicit transition variable but rather permits changes between regimes to depend on an unobserved state variable. The analysis reveals four regimes whose timing coincides with political and economic events in Ukraine. Strong coincidence between a 'high-uncertainty' regime and discretionary policy interventions suggests that policy responses to fluctuations in Ukrainian harvests may have amplified instability.